Multiple routes for non-physiological l-threonine uptake in Escherichia coli K-12 - Bubnov, Dmitrii M.; Khozov, Andrey A.; Vybornaya, Tatiana V.; Stepanova, Agnessa A.; Molev, Sergey V.; Melkina, Olga E.; Badun, Gennadii A.; Chernysheva, Maria G.; Skob, Ilia A.; Netrusov, Alexander I.; Sineoky, Sergey P. (Frontiers in Microbiology, 2025)
In this study, we identified eight multicopy suppressors (yhjE, sdaC, ydgI, alaE, ychE, yqeG, proP, and yjeM) and three distinct classes of chromosomal mutations (lrp, marC, and cycA) capable of complementing the growth defect caused by threonine uptake deficiency in the sstT tdcC livKHMGF brnQ thrP strain. YhjE, SdaC, YdgI, AlaE, mutant MarC, and CycA exhibited measurable threonine-specific uptake activity in the in vitro assay. Phenotypic assays revealed that YhjE and SdaC were the main entry points for threonine in a strain lacking major threonine-specific permeases. A derivative of the threonine-auxotrophic sstT tdcC livKHMGF brnQ thrP mutant, harboring deletions of eight multicopy suppressors, exhibited significantly reduced fitness at subsaturating threonine concentrations and improved fitness at toxic threonine concentrations, indicating a defect in membrane permeability. These results may help guide the effective construction of threonine-producing strains, extend knowledge on the substrate preferences of SdaC, AlaE, and ProP, and provide clues for further studies on the exact substrate range of YhjE, YdgI, YjeM, YchE, MarC, and YqeG whose physiologically relevant functions have not yet been established.